ENHANCED OF ELECTRIC POWER CONSUMPTION MONITORING SYSTEM IN HOUSEHOLD BASED ON SENSORLESS - Solly Aryza; Zulkarnain Lubis (Jurnal Scientia, 2023)
In the era of the industrial revolution 4.0 where electrical energy has become one aspect of life needs for humans where human electrical energy is progressing very rapidly in various fields of electronic technology. To find out how much the budget must be paid in using electrical energy, PLN made a tool that is able to find out the use of electrical energy, namely Kwh. The function of this research is to eliminate public doubts about the payment of electrical energy used every month that has been obtained. The results obtained are included in the very good category. The technology that is suitable for this problem is the Internet of Things (IoT) based electric power monitoring system technology that is able to provide accurate and real-time results. The method carried out is organized in several stages, starting from data collection, design, configuration, application.